Machinability and surface integrity analysis of Ti-17 alloy using WEDC for advanced aero-engine application - Ramatenki Chinna; Priyaranjan Sharma; Filipe Fernandes (Heliyon)
Recent advancements in aerospace industry demand intricate aero-engine parts, leading to the increased use of titanium alloys, particularly Ti-17, due to its high strength, thermal stability, and corrosion resistance. However, its low thermal conductivity and tool wear tendency pose significant machining challenges, impacting surface integrity, fatigue life, and overall component performance. This study investigates the Wire Electrical Discharge Cutting (WEDC) process, revealing that the mechanism behind improved surface integrity lies in the controlled thermal input, which minimizes phase transformations and reduces residual stresses. Experimental results reveal that rough-cutting Ti-17 yields higher surface roughness of ∼2.68 μm than that of finish cutting of ∼1.01 μm, with increased microhardness up to 80 μm depth. Further, rough cutting leads to a thicker recast layer of ∼10–15 μm, and higher residual stresses of ∼540 MPa, while finish cutting achieves a thinner recast layer of ∼2–5 μm and reduced stresses of ∼304 MPa. The innovation of this study is the investigation of WEDC behavior in Ti-17 alloy, addressing a gap in understanding its surface integrity features to improve the performance, durability, and service life of aero-engine components, advancing next-generation aerospace manufacturing.